2022
DOI: 10.1021/acs.iecr.2c02743
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Reduction of 4-Nitrophenol to 4-Aminophenol Using Ag@α-Ti(HPO4)2·H2O: Experimental and Computational Studies

Abstract: A simple hydrothermal method was developed for the synthesis of Ag supported on α-titanium bismonohydrogen orthophosphate monohydrate, Ag@α-Ti­(HPO4)2·H2O (Ag@α-TiP), using ilmenite (FeTiO3) mineral sand. The prepared nanoparticles (NPs) were characterized using powder X-ray diffraction, high-resolution transmission electron microscopy, energy-dispersive spectroscopy, X-ray photoelectron spectroscopy, and diffuse-reflectance spectroscopy. The catalytic efficiency of Ag@α-TiP NPs in the reduction of 4-nitrophen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…41 This conversion reaction proceeds through an intermediate step involving the formation of 4-nitrosophenol, which is driven by an electron transfer reaction. 42 The standard electrode potential E 0 for 4-NP/4-AP is −0.76 V, while for 43 The significant potential difference between the donor molecule (BH 4 − ) and the acceptor molecule (4-NP) creates a kinetic barrier to the reaction. 44 To overcome this kinetic barrier, precious metals are usually employed as catalysts to facilitate and promote the reaction by acceleration the electron transfer from the donor BH 4…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 This conversion reaction proceeds through an intermediate step involving the formation of 4-nitrosophenol, which is driven by an electron transfer reaction. 42 The standard electrode potential E 0 for 4-NP/4-AP is −0.76 V, while for 43 The significant potential difference between the donor molecule (BH 4 − ) and the acceptor molecule (4-NP) creates a kinetic barrier to the reaction. 44 To overcome this kinetic barrier, precious metals are usually employed as catalysts to facilitate and promote the reaction by acceleration the electron transfer from the donor BH 4…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This conversion reaction proceeds through an intermediate step involving the formation of 4-nitrosophenol, which is driven by an electron transfer reaction . The standard electrode potential E 0 for 4-NP/4-AP is −0.76 V, while for H 3 BO 3 /BH 4 – is −1.33 V . The significant potential difference between the donor molecule (BH 4 – ) and the acceptor molecule (4-NP) creates a kinetic barrier to the reaction .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, they could predict the reaction mechanism through DFT calculations. Through theoretical calculations, Thanthrige et al 114 observed that the 4-NP molecule binds to silver favorable to the −NO 2 , creating a program to convert −NO 2 into −NH 2 . Chen et al, 115 who synthesized nitrogen-doped porous carbon through algae and DFT calculations, revealed the key character of the N atoms into the carbon structure to catalyze this reaction by adjusting the carbon atoms electronic configuration followed by endorsing the adsorption of 4nitrophenolate ions on the doped carbon material.…”
Section: Theoretical Perspectivementioning
confidence: 99%